Auto-Regulation Method vs. Fixed-Loading Method in Maximum Strength Training for Athletes: A Systematic Review and Meta-Analysis - Zhang, Xing; Li, Hansen; Bi, Shilin; Luo, Yong; Cao, Yang; Zhang, Guodong (Frontiers in Physiology, 2021)
The auto-regulation method is a rising training strategy to improve strength and motor performance, and the Autoregulatory Progressive Resistance Exercise (ARPE), Rating of Perceived Exertion program (RPE), and Velocity-Based Training (VBT) are the three common auto-regulation programs. However, whether the auto-regulation method is more effective than the traditional strength training (the fixed-loading method) in maximum strength training is still unclear. The present study searched the Pubmed, SPORTDiscus, Web of Science, Embase, EBSCO, Cochrane, CNKI, and CQVIP databases, and included 8 related studies published between 2010 and 2020, with a total of 166 subjects including division 1 college players and athletes with at least one year training history, and interventions ranging from 5 to 10 weeks. A meta-analysis was performed to check the difference between the two training methods, and analyzed the differences in the existing auto-regulation programs' effectiveness. The overall results showed that the auto-regulation method was more effective than the fixed-loading method in maximum strength training (effect size = 0.64; P < 0.001; I2 = 0%). In specific, the pooled results in subgroup analysis indicated that the auto-regulation method may effectively improve the strength performance in squat (effect size = 4.64; P < 0.05; I2 = 54%) and bench press (effect size = 3.21; P < 0.05; I2 = 62%); Greater benefits of the auto-regulation method on strength improvement could be achieved in an 8- weeks or even shorter training (effect size = 0.87; P < 0.001; I2 = 0%) compared to those of 8 - 10weeks (effect size = 0.32; P < 0.001; I2 = 0%); The ARPE is the most effective training program among the three auto-regulation programs (effect size = 0.78; P < 0.001; I2 = 0%). In conclusion, the auto-regulation method could be more effective than the fixed-loading method in maximum strength training. The ARPE is a convenient and effective training program that may be considered a practical training program to replace traditional training in athletes.